Distribution of 5-Hydroxymethylcytosine in Different Human Tissues - Weiwei Li; Min Liu (Journal of Nucleic Acids)
5-hydroxymethylcytosine (5-hmC) is a modified form of cytosine recently found in mammalians and is believed, like 5-methylcytosine, to also play an important role in switching genes on and off. By utilizing a newly developed 5-hmC immunoassay, we determined the abundance of 5-hmC in human tissues and compared 5-hmC states in normal colorectal tissue and cancerous colorectal tissue. Significant differences of 5-hmC content in different tissues were observed. The percentage of 5-hmC measured is high in brain, liver, kidney and colorectal tissues (0.40–0.65%), while it is relatively low in lung (0.18%) and very low in heart, breast, and placenta (0.05-0.06%). Abundance of 5-hmC in the cancerous colorectal tissues was significantly reduced (0.02–0.06%) compared to that in normal colorectal tissues (0.46–0.57%). Our results showed for the first time that 5-hmC distribution is tissue dependent in human tissues and its abundance could be changed in the diseased states such as colorectal cancer.